Leptin receptor gene Gln223Arg polymorphism is not associated with obesity and metabolic syndrome in Turkish children - Komşu-Örnek, Zuhal; Demirel, Fatma; Dursun, Ahmet; Ermiş, Bahri; Pişkin, İ. Etem; Bideci, Aysun (The Turkish Journal of Pediatrics, 2012)
The aim of the study was to investigate the relationship between leptin receptor gene (LEPR) Gln223Arg polymorphism and obesity in Turkish children. Ninety-two obese and 99 lean children (between 5-15 years) were included in the study. Twenty-three of the obese children were diagnosed with metabolic syndrome. Blood samples were collected for morning fasting blood glucose, insulin, leptin, and lipid level measurements. LEPR Gln223Arg polymorphism was analyzed by restriction fragment length polymorphism. Significant differences were observed in anthropometric measurements, fasting blood glucose, insulin, leptin, and lipid levels between obese and lean children. Serum leptin levels were markedly higher in obese children. No significant association was noted between Gln223Arg polymorphism and serum leptin, insulin and lipid levels. There were no differences in the genotype frequencies or allele distribution for Gln223Arg polymorphism among obese, obese with metabolic syndrome and lean children. Our findings suggest that there is no association between Gln223Arg polymorphism and obesity in Turkish children.